OP0056 Can We Replace Temporal Artery Biopsy with Cranial Ultrasound for the Diagnosis of GIANT Cell Arteritis? A Retrospective Cohort Study of the Diagnostic Utility of Ultrasound in Routine Clinical Practice. (10th June 2014) - Croft, A.; Thompson, N.; Duddy, M.; Khattak, F.; Mollan, S.; Jobanputra, P.
Abstract : Background: Temporal artery biopsy (TAB) has historically been considered the "gold standard" diagnostic test for Giant Cell Arteritis (GCA). Objectives: The aim of this study was to evaluate the diagnostic utility of cranial duplex ultrasound (CDUS) in patients with a suspected diagnosis of GCA in routine clinical practice. Methods: All patients undergoing CDUS between Jan 2005 and July 2013 were identified and clinical data obtained from electronic records, and, if necessary primary care providers. American College of Rheumatology (ACR) criteria for GCA were used to classify patients. US reports were independently classified according to whether there was evidence of an arteritis or not. Explicit US features of GCA such as a halo sign were not required to make this determination. The relationship between the ACR criteria alone or in combination with US and a final clinical diagnosis of GCA (made after a minimum of 3-month follow-up) was analysed. A clinical diagnosis of GCA after 3 months of follow up served as our gold standard. The sensitivity and specificity of CDUS and of TAB were examined against our gold standard. Results: A total of 87 patients underwent CDUS for suspected GCA. 36 patients (41%) had a confirmed clinical diagnosis at 3-month follow-up. When compared to clinical diagnosis at 3 months, the sensitivity of CDUS was 81%, specificity 98%, positive likelihood ratio 41, negative likelihood ratio 0.2, positive predictive value of 97% and negative predictive value of 88%. In contrast, when compared to clinical diagnosis at 3 months TAB had a sensitivity of 53%, specificity 100%, positive likelihood ratio 2.3, negative likelihood ratio 0.2, positive predictive value of 100% and negative predictive value of 47%. Detailed data for comparison of ACR criteria and ultrasound for prediction of 3-month clinical diagnosis is shown in Table 1 . Conclusions: CDUS had a greater sensitivity than TAB and a comparable specificity to diagnose GCA. The CDUS result was the strongest predictor for a diagnosis of GCA at 3 months, whereas ACR criteria when used alone were insufficiently specific to accurately predict or exclude the diagnosis of GCA at 3 months. In contrast, the high positive and negative predictive value of CDUS over TAB indicates that TAB may be unnecessary particularly where clinical suspicion of GCA is high or quite low. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4734